Béla Bartók’s Concept of ‘Genuine and Valuable Art’ - Somfai, László (Danish Yearbook of Musicology, 2005)
Béla Bartók did not intend to write progressive world music or to create any kind of international musical language rather his ideal was to build up a great Hungarian national art, a ‘comprehensive art’. He did not identify himself with nationalism in general; national idiom as a principle, without the manifestation of a genius, was no value for him. In contrast to the typical national composer with a passionate interest in the music or folk music of his homeland, Bartók had a multi-ethnic background (Hungarian, Rumanian, Slovak, Ruthenian, and Arab rural music). Folk-music arrangements of different kinds make up a substantial part of the oeuvre, but the creation of folklore imaginaire (Bartók’s expression) interested him even more. Two short case studies detect compositional strategies in original compositions connected with indirect folk-music influences. In the two-movement structure of the Second Sonata for Violin and Piano (1922), without quoting folk music, with the variant forms of the opening theme Bartók recreated the evolution of folk music in miniature, from a Rumanian hora lunga-like improvisational concept to the developed stanza formation. In the overall sonata form of the First Movement of the Second Piano Concerto (1930/31) the trumpet motto, an emphatically non-Hungarian motive theme (the first notes were borrowed from Stravinsky’ Firebird) plays a crucial role: in retrograde inversion it creates a warm, pathetic Hungarian climax.